Metal-Doped Lead Halide Perovskites: Synthesis, Properties, and Optoelectronic Applications - Zhou, Yang; Chen, Jie; Bakr, Osman M; Sun, Hong-Tao (Chemistry of materials, 2018)
Doping of lead halide perovskites (LHPs) with the targeted impurities has emerged as an additional lever, a dimension beyond structural perfection and compositional distinction, for the alteration of many properties of halide perovskites. The past several years has seen an explosive increase in our knowledge of doped halide perovskites, which exhibit distinct optical and electronic properties with respect to undoped counterparts and improve performance of perovskite optoelectronic devices. However, there are still a series of fundamental scientific issues unresolved in the domain of doped perovskites. In this review, we present a critical overview of recent advances in the synthesis, property, and functional applications of metal-doped halide perovskites. We lay a particular focus on three-dimensional LHPs and discuss the influence of doped metal ions on the properties of these perovskites, including main group metal cations, transition metal cations, and rare earth (RE) metal cations. We thoroughly summarize the synthesis methods used, doping-induced variation in optoelectronic properties, and benefit of doping engineering for optimization of device performance. We highlight the milestone achievements in this field and emphasize new properties arising from dopants in halide perovskites. We also address controversies encountered during the development of doped perovskites and examine the remaining challenges in this exciting field of science. Finally, we present our perspectives for further investigation of this star material by doping engineering.